PENGARUH SUKU BUNGA SBI, NILAI TUKAR, INFLASI DAN INDEKS DOW JONES TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BEI - Sudarsana, Ni Made Anita Dewi; Candraningrat, Ica Rika (E-Jurnal Manajemen, 2014)
Composite Stock Price Index (CSPI) is a reflection of the Indonesian economy. The CSPI showed significant improvement of the Indonesian economy is in a state that is conducive and vice versa. To be able to know what can help improvement of CSPI consider several factors such as the SBI interest rate, inflation, exchange rate and global stock markets like the Dow Jones Industrial Avarage (DJIA). The purpose of this study was to determine the effect of the SBI interest rate, exchange rate, inflation and the Dow Jones Indeks (DJIA) on CSPI. The research was conducted on the Stock Exchange by using  sample of 72 consisted of the entire variable monthly data during 2008 to 2013 with the selection of the sample through a non probabability sampling method by purposive sampling method and the data were analyzed with multiple linear regression analysis techniques. Based on the analysis found SBI interest rates, inflation, exchange rates and Dow Jones index simultaneously affect the CSPI. SBI interest rates, inflation and exchange rate partially significant negative effect on the CSPI, this means an increase in SBI rates, inflation and the exchange rate may result decrease value of  CSPI whereas Dow Jones indeks is partially significant positive effect on CSPI. This means that the increase occurred in the Dow Jones indeks can increase the value of CSPI. Composite Stock Price Index (CSPI) is a reflection of the Indonesian economy. The CSPI showed significant improvement of the Indonesian economy is in a state that is conducive and vice versa. To be able to know what can help improvement of CSPI consider several factors such as the SBI interest rate, inflation, exchange rate and global stock markets like the Dow Jones Industrial Avarage (DJIA). The purpose of this study was to determine the effect of the SBI interest rate, exchange rate, inflation and the Dow Jones Indeks (DJIA) on CSPI. The research was conducted on the Stock Exchange by using  sample of 72 consisted of the entire variable monthly data during 2008 to 2013 with the selection of the sample through a non probabability sampling method by purposive sampling method and the data were analyzed with multiple linear regression analysis techniques. Based on the analysis found SBI interest rates, inflation, exchange rates and Dow Jones index simultaneously affect the CSPI. SBI interest rates, inflation and exchange rate partially significant negative effect on the CSPI, this means an increase in SBI rates, inflation and the exchange rate may result decrease value of  CSPI whereas Dow Jones indeks is partially significant positive effect on CSPI. This means that the increase occurred in the Dow Jones indeks can increase the value of CSPI.
Keywords: CSPI, SBI, inflation, exchange rate, DJIA